Mass unemployment and the state - Lindvall, Johannes (Oxford : Oxford University Press, 2010)
'Mass Unemployment and the State' shows that domestic political arrangements have mattered greatly to the economic and labor market policies that European governments pursued in response to the problem of unemployment from the early 1970s to the present day.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Unemployment -- Government policy -- Europe; Unemployment -- Government policy -- Europe -- History